From the Cajal alumni Achúcarro and Río-Hortega to the rediscovery of never-resting microglia - Tremblay, Marie-Ève; Lecours, Cynthia; Samson, Louis; Sánchez-Zafra, Víctor; Sierra, Amanda (Frontiers in Neuroanatomy, 2015)
Under the guidance of Ramón y Cajal, a plethora of students flourished and began to apply his silver impregnation methods to study brain cells other than neurons: the neuroglia. In the first decades of the XXth century, Nicolás Achúcarro was one of the first researchers to visualize the brain cells with phagocytic capacity that we know today as microglia. Later, his pupil Pío del Río-Hortega developed modifications of Achúcarro´s methods and was able to specifically observe the fine morphological intricacies of microglia. These findings contradicted Cajal´s own views on cells that he thought belonged to the same class as oligodendroglia (the so called “third element” of the nervous system), leading to a long-standing discussion. It was only in 1924 that Río-Hortega´s observations prevailed worldwide, thus recognizing microglia as a unique cell type. This late landing in the Neuroscience arena still has repercussions in the XXIst century, as microglia remain one of the least understood cell populations of the healthy brain. For decades, microglia in normal, physiological conditions in the adult brain were considered to be merely “resting”, and their contribution as “activated” cells to the neuroinflammatory response in pathological conditions mostly detrimental. It was not until microglia were imaged in real time in the intact brain using two-photon in vivo imaging that the extreme motility of their fine processes was revealed. These findings led to a conceptual revolution in the field: “resting” microglia are constantly surveying the brain parenchyma in normal physiological conditions. Today, following Cajal’s school of thought, structural and functional investigations of microglial morphology, dynamics, and relationships with neurons and other glial cells are experiencing a renaissance and we stand at the brink of discovering new roles for these unique immune cells in the healthy brain, an essential step to understand their causal relationship to diseases.